Analysis of the Effect of Financial Literacy and Hedonism Lifestyle on Investment Preferences in Generation Z Mediated by Financial Technology - Riani Sukma Wijaya; Muhamad Irfan Florid (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Over the past few years, Gen Z's interest in investment has increased, along with the growing popularity of financial technology (fintech) applications that provide easy access to various investment instruments, such as stocks, mutual funds, and cryptocurrencies. Although Gen Z has wider access to various investment products through fintech, the low level of financial literacy and the influence of hedonism lifestyle are still the main obstacles in making wise investment decisions. This study uses a quantitative approach with an explanatory research design that aims to explain the cause-and-effect relationship between financial literacy, hedonism lifestyle, financial technology (fintech) as a mediating variable, and investment preferences in Generation Z. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method was used to analyze the data, with 200 samples of students who have made investments. Based on the results of the study, it can be concluded that financial literacy affects investment preferences in generation Z, hedonism lifestyle affects the investment preferences of generation Z, financial literacy moderated by financial technology affects investment preferences in generation Z. Hedonism lifestyle moderated by financial technology has no effect on investment preferences in Generation ZThis study uses a quantitative approach with a small sample so that the research results are not accurate. Based on this, for further research it is necessary to conduct empirical studies with a wider sample to ascertain what the implications of this research are.